Analisis Penggunaan Bahasa Indonesia dalam Penyusunan Surat Menyurat dan Dampak Terhadap Efisiensi Manajemen Perkantoran - Aprilianti, Anisa; Ramadhani, Annisha Dita; Mulyadi, Arif; Erlangga, Arli; Dealova, Defia; Mochamad Whilky Rizkyanfi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the good and correct use of Indonesian in the preparation of correspondence in the office environment and examine its impact on the efficiency of office management. This research uses the library research method by examining various written sources, such as scientific journals, books, and relevant official documents. The analysis was carried out in a qualitative descriptive manner to identify the relationship between the use of language in accordance with the rules and the effectiveness of administrative communication. The results of the study show that the use of Indonesian in accordance with the grammar, spelling, and structure of official letters can improve information clarity, minimize misunderstandings, and speed up communication flows in managerial activities. Management efficiency is achieved through reduced correction time and increased accuracy in message delivery. Therefore, improving employees' language competence through routine training is highly recommended as part of a strategy to improve the quality of office management.